ER-Mitochondria Crosstalk during Cerebral Ischemia: Molecular Chaperones and ER-Mitochondrial Calcium Transfer - Yi-Bing Ouyang; Rona G. Giffard (International Journal of Cell Biology)
It is commonly believed that sustained elevations in the mitochondrial matrix Ca2+ concentration are a major feature of the intracellular cascade of lethal events during cerebral ischemia. The physical association between the endoplasmic reticulum (ER) and mitochondria, known as the mitochondria-associated ER membrane (MAM), enables highly efficient transmission of Ca2+ from the ER to mitochondria under both physiological and pathological conditions. Molecular chaperones are well known for their protective effects during cerebral ischemia. It has been demonstrated recently that many molecular chaperones coexist with MAM and regulate the MAM and thus Ca2+ concentration inside mitochondria. Here, we review recent research on cerebral ischemia and MAM, with a focus on molecular chaperones and ER-mitochondrial calcium transfer.